Emergent measles-containing vaccination recommendation for aged 6–11 months and detection of vaccine-associated measles during a large measles outbreak in Okinawa, Japan, in 2018. Issue 10 (28th February 2020) - Kuba, Yumani; Kyan, Hisako; Iha, Yoshiyuki; Kato, Takashi; Oyama, Minori; Miyahira, Masato; Kakita, Tetsuya; Takara, Taketoshi; Yamauchi, Miyuki; Kamiya, Hajime; Sunagawa, Tomimasa; Kawakami, Yoshino; et al.
Abstract: Okinawa Prefecture, Japan, experienced a large measles outbreak from March to May 2018. During this outbreak, there were 99 laboratory-confirmed cases and 14 vaccine-associated measles cases. In addition to the reinforcement of routine immunization, Okinawa prefectural government introduced emergent measles-containing vaccination recommendations for infants aged 6–11 months as part of the outbreak response. Increased concern exists in Okinawa about measles in infants following a previous outbreak from 1998 to 2001, when nine children including four infants died. Of 8062 infants aged 6–11 months who received measles-containing vaccine (MCV), six developed vaccine-associated measles; incidence was 0.74 per 1000 doses (95%CI 0.27–1.62). This was similar to that of first dose routine immunization recipients at one year of age (IR 0.60, 95%CI 0.20–1.78). Among 14 vaccine-associated measles cases, throat swab samples showed the highest positive rate (92.9%) by real-time reverse transcription polymerase chain reaction (RT-qPCR), followed by urine (25.0%) and whole blood (7.7%) samples. Furthermore, one throat swab sample classified as equivocal by RT-qPCR was positive by conventional RT-PCR (RT-PCR). During an outbreak, it is critical to distinguish between cases with measles-like symptoms caused by wild circulating virus and those caused by vaccine-derived virus as accurately and urgently as possible because the public health response will be quite different. No infant deaths were observed during this outbreak, and no severe adverse events following immunization were seen among infants 6–11 months old who were given MCV as a public health response. Thus, we conclude that introduction of emergent MCV was effective and describing the characteristics of vaccine-associated measles cases during a measles outbreak will be helpful for future outbreak response efforts.